ALGINATE COATED MgO-NPs IMPROVES THE STABILITY OF Kluyveromyces lactis β-GALACTOSIDASE FOR BIOTECHNOLOGICAL APPLICATIONS - Shakeel Ahmed Ansari; Rukhsana Satar; Nadeem Ikram; Muhammad Awais (Química Nova, 2023)
The current study was undertaken to immobilize Kluveromyces lactis β-galactosidase on alginate coated magnesium oxide nanoparticles (ACMONPs). Transmission electron microscopy showed that MgO-NPs synthesized by wet chemical approach were of 27 nm size and spherical in shape. Excellent biocompatibility of sodium alginate resulted in 90% immobilization yield for β-galactosidase due to covalent attachment. Soluble and immobilized β-galactosidase exhibited its pH and temperature-optima at pH 7.0 and at 40 °C, respectively. However, the enzyme attached to ACMONPs enhanced its activity at higher and lower pH and temperature ranges, in contrast to enzyme in solution. ACMONPs bound enzyme displayed greater enzyme activity under the effect of galactose mediated product inhibition as well as in reusability experiment. Our study indicated that 88% lactose was hydrolyzed by β-galactosidase immobilized on ACMONPs at 40 °C as compared to 71% by soluble enzyme under identical temperature in controlled batch reactors. Hence, this nanomatrix can find its potential application in continuous packed-bed reactors for obtaining lactose-free dairy products.